A block of Ramesses II reused as a threshold in the Wakala of Qawsun (Cairo). Issue 1 (January 2013) - Lorand, David
Publication of a lintel/architrave of Ramesses II probably from Heliopolis re-used as a threshold in medieval Cairo.